2012
DOI: 10.4238/2012.april.10.6
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase enhancer region polymorphism not related to susceptibility to acute lymphoblastic leukemia in the Kashmir population

Abstract: ABSTRACT. Thymidylate synthase (TS) is a crucial enzyme in folate metabolism and plays a vital role in DNA synthesis and repair. The most common polymorphism in TS is a unique double (2R) or triple (3R) 28-bp tandem repeat sequence in the enhancer region of the TS gene (TSER). This genetic variation in TSER has been widely investigated and has been implicated as a risk factor for the development of various cancers, including acute lymphoblastic leukemia. It has also been found to influence sensitivity to anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
(25 reference statements)
2
7
0
Order By: Relevance
“…European populations also confirmed the interethnic differences in the distribution of the investigated polymorphism. 19 In the present study, the allele and genotype frequencies for the rs2790 A > G polymorphism in patients with ALL were similar to those in the Chinese samples of the 1000 Genomes Project, potentially indicating no significant effects of the studied polymorphism on the risk for ALL. The protective role of the rs34743033 3R allele was reported in a population which consisted of 71 adult patients with ALL.…”
Section: Effects Of the Tyms Rs2790 A > G Polymorphism On Haematolosupporting
confidence: 79%
See 1 more Smart Citation
“…European populations also confirmed the interethnic differences in the distribution of the investigated polymorphism. 19 In the present study, the allele and genotype frequencies for the rs2790 A > G polymorphism in patients with ALL were similar to those in the Chinese samples of the 1000 Genomes Project, potentially indicating no significant effects of the studied polymorphism on the risk for ALL. The protective role of the rs34743033 3R allele was reported in a population which consisted of 71 adult patients with ALL.…”
Section: Effects Of the Tyms Rs2790 A > G Polymorphism On Haematolosupporting
confidence: 79%
“…18 However, no statistically significant association of rs34743033 polymorphism on the susceptibility to ALL was found in a Kashmir population. 19 In the present study, the allele and genotype frequencies for the rs2790 A > G polymorphism in patients with ALL were similar to those in the Chinese samples of the 1000 Genomes Project, potentially indicating no significant effects of the studied polymorphism on the risk for ALL. However, this finding needs validation in a well-designed case-control study.…”
Section: Several Studies In American Andsupporting
confidence: 79%
“…IHC detects TS expression at protein level, while RT-PCR assays at mRNA level. Several studies have reported some discrepancy between mRNA expression and protein expression for TS [24,39,40]. A recent research by Hou.et.al found that very high protein expression of TS determined by IHC correlates well with TS mRNA expression, while low protein expression of TS correlates poorly with TS mRNA expression [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, no association has been established between the TYMS 5'-UTR VNTR polymorphism and the incidence of gastric tumors, breast cancer, or leukemia (Nazki et al, 2012;Quintero-Ramos et al, 2014;Araújo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%